Penyuluhan Demam Berdarah dan Pelatihan Pembuatan Alat Perangkap Nyamuk sebagai Upaya Pencegahannya di SDN 09 Pontianak Timur: Counseling on Dengue Fever and Training in Making Mosquito Trapper as Prevention Efforts at SDN 09 Pontianak Timur - Wahdaningsih, Sri; Hestiva, Hestiva (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Dengue fever has become a health problem in global society, including in Indonesia. The number of cases increased until the end of 2023 with the number of cases reaching 4,304 cases and the number of deaths reaching 48 cases in West Kalimantan. The emergence of dengue fever cases makes all levels of society anxious and worried because it can cause death in a short time. Efforts are needed to control dengue fever by increasing public knowledge about dengue fever and how to prevent it can be an alternative way. The aim of this activity is to provide health education about dengue fever and efforts to prevent it through the practice of making mosquito traps. The method used was a lecture using PowerPoint media and continued with training in making mosquito traps. The activity was held on Tuesday, January 9 2024 at SDN 09 East Pontianak attended by 42 participants and went well and smoothly according to plan. After being given counseling, there was an increase in participants' understanding based on the results of the average pre-test and post-test scores. During the activity, participants were active and able to answer the questions given correctly. Next, participants were invited to practice directly making mosquito traps from used bottles. During the training process, participants were enthusiastic and followed directions correctly. It was concluded that this activity was useful in increasing students' knowledge and awareness in preventing fever.